Peningkatan Akses Informasi Lingkungan melalui Pemasangan Plang Gang dan Nomor Rumah di Desa Anggut Bawah RT 03 - Anggi Dela Permata Sari; Anas Abdul Haqqi; Duratul Nada Azura; Fajar Amrullah; Zefri Oktober; Evryeni Jusmadi; Hendri Alamsyah; Ami Pradana (Jurnal Dehasen Mengabdi, 2026)
Limited access to environmental information remains a challenge in Anggut Bawah Village RT 03, particularly due to the absence of clear alley signs and house numbering. This condition complicates navigation for visitors, public service officers, and administrative processes. This community service activity aims to improve access to environmental information through the installation of alley name signs and house numbers. A participatory approach was applied by actively involving residents in the stages of observation, planning, and installation. The results indicate that the RT 03 environment has become more organized, easier to identify, and more supportive of orderly administration and public services. Additionally, this program increased community awareness of the importance of environmental identity as part of effective local governance.